2009
DOI: 10.1080/15567260903058033
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Solid State/Fluidic Cooling for Hot Spot Removal

Abstract: In this article we describe a novel cooling scheme utilizing a combination of fluidic (single-phase convection and phase change) and solid-state (superlattice cooler) techniques to simultaneously remove high background heat fluxes (,100 W/cm 2 ) over the entire chip and dissipate ultra high heat fluxes (,0.5-1 kW/cm 2 ) from multiple localized hot spots. This article focuses on the conceptual design to assess the feasibility of the proposed cooling scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Through modeling, device fabrication, and testing of the above Hybrid Cooling Scheme, it was found that the optimum current of the SLC is a function of the superlattice size, ambient temperature, ground electrode location, as well as the thermal and interface resistance [14]. The optimum current increases with the superlattice size and ambient temperature.…”
Section: Hybrid Cooling Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Through modeling, device fabrication, and testing of the above Hybrid Cooling Scheme, it was found that the optimum current of the SLC is a function of the superlattice size, ambient temperature, ground electrode location, as well as the thermal and interface resistance [14]. The optimum current increases with the superlattice size and ambient temperature.…”
Section: Hybrid Cooling Schemementioning
confidence: 99%
“…The electrical current can spread to the substrate as heat flow spreads. The model that Sahu et al reported [14] could be used in this model, however, we leave this factor as a perfect electrode (zero resistance) to avoid the complexity. Current density through the silicon substrate is much lower than through the SLC device.…”
Section: Spreading Joule Heating In Silicon Substratementioning
confidence: 99%
“…The main issue is the extreme temperature that results at the hot spots. It is known that next generation electronic chips are expected to produce around 500 W cm -2 as the background and over 1000 W cm -2 at the hot spots [1][2]. Special application microelectronics already need adequate efficient cooling for background heat fluxes as high as several kilowatts per square centimeter with hot spots having an order of magnitude higher heat fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Hot spots and non-uniform temperature distribution in the chip can degrade the performance and reduce the reliability. Unfortunately, most of the existing cooling techniques can not remove the hot spots selectively and they have to operate in a sub-optimal fashion and over-cool the whole chip [7]. To overcome these difficulties, one solution is to use hybrid solid-state and liquid cooling.…”
Section: Introductionmentioning
confidence: 99%
“…According to ref [7] spot cooling inside a microchannel can be used for bubble condensation and the control of the two-phase flow. In this application, it is important to study the maximum cooling and cooling power density of the solid-state cooler as a function of the flow parameters, heat transfer coefficient and the liquid temperature.…”
Section: Introductionmentioning
confidence: 99%